COMPARISON BETWEEN 18F-PSMA AND 18F-FDG RADIOTRACERS FOR PET/CT IN THE EVALUATION OF PATIENTS WITH METASTATIC MELANOMA - Thiago Soare Rocha Alves; Diego Mendanha; Ellen Lima; Natália Tobar; Juliana Souza; Ligia Macedo; Allan Oliveira Santos; Mariana Cunha Lopes Lima; Elba Etchebehere; Carmen Silva Passos Lima (Hematology, Transfusion and Cell Therapy)
Introduction/Justification: PET/CT has emerged in the last two decades as a dominant imaging modality used for staging, monitoring response and surveillance of melanoma using 18F-FDG as radiotracer. Recent publications have demonstrated the possibility of use of 18F-PSMA PET/CT as an additional resource to the evaluation of melanoma, due to the expression of Prostate-Specific Membrane Antigen protein (PSMA) in these cancer cells and because anti-PSMA antibodies react with malignant melanoma neo vasculature. Objectives: Would 18F-PSMA PET/CT have the potential role of a novel diagnostic imaging technique in melanoma cases? Materials and Methods: Eleven participants with diagnoses of metastatic melanoma underwent 18F-FDG PET/CT and 18F-PSMA PET/CT (24-hours interval), and the lesions uptakes were evaluated with both radiotracers. The results were grouped in three categories: A - greater expression of 18F-PSMA compared to 18F-FDG; B – equivalent uptake between the radiotracers; and C - greater expression of 18F-FDG compared to 18F-PSMA. Results: 18,1% of participants were in category A, 54,5% in category B and 27,2% in category C. The lesions with greater 18F-PSMA uptake compared to 18F-FDG were mainly in the brain, lungs, adrenals, and scattered throughout the chest. Furthermore, one subjects presented only 18F-PSMA uptake in brain metastasis, showing the importance of this method to the clinical follow-up of these patients. Our findings align with the Chang et al.’s, who demonstrated in vitro expression of PSMA in the neovasculature of melanoma lesion and with Snow et al.’s who observed PSMA positivity in endothelial cells of capillaries within stage III/IV melanoma metastases. Conclusion: Therefore, apart from the use of 18F-PSMA PET/CT in staging prostate cancer patients, this method shows a great potential in the evaluating of metastatic melanoma, still needing further and longer studies to confirm these advantages.